Immediate and long-term effects of zero-drop running shoes on lower extremity biomechanics - Liu, Zimeng; Zhou, Yulin; Liu, Hui; Cheng, Peng; Zheng, Zhiyi; Zeng, Quanshou (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe purpose of the study was to investigate the immediate and long-term effects of zero-drop running shoes on lower extremity joint biomechanics.MethodsSeven male runners participated in this study (height: 1.74 ± 0.03 m, weight: 62.5 ± 3.1 kg, body mass index: 20.6 ± 0.7 kg/m2). Kinematic and kinetic data were collected when the participants ran at a speed of 13 ± 0.65 km/h in running shoes with zero and 15 mm drop both immediately and after the 8-week intervention wearing zero-drop running shoes. Paired t-tests were used to analyze the biomechanical differences between the different drop shoes in the immediate test and the biomechanical changes during the intervention.ResultsThe foot strike index increased (zero-drop: p = 0.021, 15 mm drop: p = 0.049), along with the negative work of ankle joint (15 mm drop: p = 0.018), and the hip joint (zero-drop: p = 0.004, 15 mm drop: p = 0.009), while metatarsophalangeal joint negative work decreased (zero-drop: p = 0.029, 15 mm drop: p = 0.028) in post-intervention test compared to the pre-intervention test.ConclusionZero-drop running shoes promote a forefoot strike pattern, which affects the distribution of lower extremity joint work.